Financial Market Constraints and Private Investment in a Developing Country - Johnson, Omotunde (Washington, D.C. : International Monetary Fund, 1990)
Firms in developing countries that seek outside financing for investment must often choose their debt-equity combinations in the face of financial market constraints on debt service, on outside equity financing, and on internal finance (endowments). Inefficiencies in the allocation of available finance and in the equity-debt choices that can ensue can be prevented by appropriate policy measures to improve information on profitable investment opportunities and about firms; to directly strengthen financial intermediation; and to support appropriate credit guarantee schemes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet